Pathways of rural development in Madagascar: an empirical investigation of the critical triangle of environmental sustainability, economic growth, and poverty alleviation - Zeller, Manfred; Lapenu, Cecile; Minten, Bart; Ralison, Eliane; Randrianaivo, Desire; Randrianarisoa, Claude (International Food Policy Research Institute, 2000)
This paper is based on community-level data from 188 villages in rural Madagascar. The survey that was conducted in 1997 made extensive use of long-term recall questions ascertaining changes during the past 10 years in rice yields, wages, population, soil fertility, and other pertinent variables of rural development. We find that—on average for all villages—the yields of irrigated rice, the major food crop, and real agricultural wages declined, while the communities expanded their upland area by nearly a quarter and experienced deteriorating fertility of their upland soils. These patterns are consistent with the wide-held belief that rural areas in Madagascar have witnessed increased poverty, economic stagnation, and a continued degradation of the natural resources. Yet, the five agroecological regions in our sample exhibit quite different patterns of rural development, and at least one of them has experienced increases in yields and wages. From a policy perspective, it is important to better understand the driving forces of such diverse rural change. The overall decline in rural wages over the past 10 years is expected to have contributed to increased poverty, food insecurity and malnutrition in rural areas, as rural wage laborers traditionally belong to the poorest of the poor in Madagascar. In this paper, we present an econometric analysis of the determinants of and interdependencies between the three components of sustainable development: economic growth, environmental sustainability, and poverty alleviation.